Lessons learned from the pilot study of an orthostatic hypotension intervention in the subacute phase following spinal cord injury. (30th September 2019) - Moineau, Bastien; Brown, Andrea; Brisbois, Louise; Zivanovic, Vera; Miyatani, Masae; Kapadia, Naaz; Hsieh, Jane T. C.; Popovic, Milos R.
Abstract : Context : Following spinal cord injury (SCI) at the cervical or upper-thoracic level, orthostatic hypotension (OH) is observed in 13–100% of patients. This study aimed to test the feasibility of conducting a randomized controlled trial combining a dynamic tilt-table (Erigo ® ) and functional electrical stimulation (FES) to mitigate OH symptoms in the subacute phase after SCI. Design : Pilot study. Setting : A tertiary rehabilitation hospital. Participants : Inpatients who had a C4-T6 SCI (AIS A-D) less than 12 weeks before recruitment, and reported symptoms of OH in their medical chart. Interventions : Screening sit-up test to determine eligibility, then 1 assessment session and 3 intervention sessions with Erigo ® and FES for eligible participants. Outcome measures : Recruitment rate, duration of assessment and interventions, resources used, blood pressure, and Calgary Presyncope Form (OH symptoms). Results : Amongst the 232 admissions, 148 inpatient charts were reviewed, 11 inpatients met all inclusion criteria, 7 participated in a screening sit-up test, and 2 exhibited OH. Neither of the two participants recruited in the pilot study was able to fully complete the assessment and intervention sessions due to scheduling issues (i.e. limited available time). Conclusion : This pilot study evidenced the non-feasibility of the clinical trial as originally designed, due to the low recruitment rate and the lack of available time for research in participant's weekday schedule. OH in the subacute phase after SCI was less prevalent and less incapacitating than expected. Conventional management and spontaneous resolution of symptoms appeared sufficient to mitigate OH in most patients with subacute SCI.